QTL detection for fruit shelf life and quality traits across segregating populations of tomato - Pereira Da Costa, Javier Hernán (2013)
The aim of this work was to detect QTLs associated with fruit shelf life and quality traits across different segregating populations derived from an interspecific cross. The first backcross generation (BC1) of an interspecific tomato cross was analyzed to detect genomic regions from Solanum pimpinellifolium accession LA722 that could improve fruit quality and prolonging fruit shelf life in an Argentinean cultivar. Families derived from five BC1 self-plant and BC2 were used to validate the detected QTL in the BC1 as well as to identify regions with wild type recessive alleles of QTLs controlling these traits. Thirty polymorphic markers (SSR) in parental genotypes and F1 were used to analyze the segregating populations. The comparison among QTLs detected in the BC1 and BC2 generations and the families BC1S1 allowed assessing the consistency of six QTLs for length, shape, weight, pH, soluble solids content and fruit shelf life. QTLs with recessive effects from wild parent prolonging fruit shelf life were found and it was possible to detect QTLs for quality traits that have not been previously reported. This finding provides alternative genes for breeding programs that attempt to improve the color, soluble solids content and fruit shelf life of tomato fruits.